2016
DOI: 10.1155/2016/2676589
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Promising Technologies for 5G Networks

Abstract: As an enhancement of cellular networks, the future-generation 5G network can be considered an ultra-high-speed technology. The proposed 5G network might include all types of advanced dominant technologies to provide remarkable services. Consequently, new architectures and service management schemes for different applications of the emerging technologies need to be recommended to solve issues related to data traffic capacity, high data rate, and reliability for ensuring QoS. Cloud computing, Internet of things … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 98 publications
(97 reference statements)
1
39
0
2
Order By: Relevance
“…The authors discussed the challenges, technologies, and implementation issues of these networks. Le et al [49] presented the technology enablers for 5G communication and security challenges of the emerging technologies. From these studies, it can be marked that the security is a significant constraint for the 5G architecture and to facilitate the reliable services on the mobile communication it is necessary to consider privacy and trust of the user.…”
Section: Existing Surveys and Their Applicabilitymentioning
confidence: 99%
“…The authors discussed the challenges, technologies, and implementation issues of these networks. Le et al [49] presented the technology enablers for 5G communication and security challenges of the emerging technologies. From these studies, it can be marked that the security is a significant constraint for the 5G architecture and to facilitate the reliable services on the mobile communication it is necessary to consider privacy and trust of the user.…”
Section: Existing Surveys and Their Applicabilitymentioning
confidence: 99%
“…Telecom operators observe the technical challenges of IoT through systems, tools, devices, and platforms because their availability and integration complexity determines the opportunity to capture a share of the value that is generated by IoT implementation. Based on the literature review, it was found that the most commonly mentioned terms in this sense were related to: (1) ticketing system [201]; (2) monitoring: devices [199,[201][202][203][204]/services [199,201,202,205,206]/tools [207]/systems [11,12,199,201,205,206,[208][209][210]/ data [95,201]/framework [12,201]/solutions [20,205]/networks [211]/process [7]/activity [203,204,207]; (3) tracking technologies [4]/devices [204]/systems [204]/applications [11,210]/system [201]/services [202,205]; (4) [95,199]. This has led us to identify four activities, i.e., ticketing, monitoring, tracking, and managing/controlling, as new classification criteria of IoT applications.…”
Section: Activity-based Classification Of Iot Applicationsmentioning
confidence: 99%
“…Authors compare these technologies and try to implement them through prototypes, or test the combination of these technologies. However, other technologies exist, such as cloud-RAN [7], Coordinated Multi-Point (CoMP), White Space Spectrum [208], which are not in the scope of this paper.…”
Section: Other Technologiesmentioning
confidence: 99%
“…Since V2X covers a wide range of aspects of the smart-connected car, the limitation of short-range connectivity results from IEEE 802.11p and DSRC motivates to explore new communication technologies. To the best of our knowledge, the fastest wireless network is LTE-Advanced (LTE-A), and 5G networks are an actively on-going research area [16,17]. Furthermore, 5G is expected to bring new capabilities to the smart-connected car due to extreme broadband, ultra-low latency, and edgeless connectivity [18].…”
Section: The Overview Of Vehicle-to-everythingmentioning
confidence: 99%